INVESTIGATING THE RELATIONSHIP BETWEEN PROBLEMATIC INTERNET USE AND MENTAL HEALTH OUTCOMES AMONG YOUTHS - Dar, Ashak Hussain (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study investigates the relationship between problematic internet use and mental health outcomes among youth. Specifically, it aims to examine the levels of internet addiction and mental health among college students in the Kashmir valley, considering factors such as gender and domicile (rural/urban). The sample consists of 100 college students (50 males and 50 females, with equal representation from rural and urban areas) randomly selected from colleges in Srinagar. The Internet Addiction Scale by Kimberly Young is employed to assess internet addiction levels. The study hypothesizes significant differences in internet addiction and mental health based on gender and domicile, as well as a positive correlation between internet addiction and poor mental health outcomes among the youth population studied. The findings could provide valuable insights into the potential impact of problematic internet use on the mental well-being of young individuals, informing preventive measures and intervention strategies.